The synthesis and characterization of films and nanofibers from novel poly(N,N'-dimethyl acrylamide)-graft-poly(dimethyl siloxane) amphiphilic hydrogels - Wagenaar, Stefan (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.